Assessment of Risk Factors of Hepatotoxicity among Tuberculosis Patients - Wardhana, Muhammad F.; Milanda, Tiana; Sumiwi, Sri A. (Universitas Padjadjaran, Indonesia)
Tuberculosis is a devastating disease caused by Mycobacterium tuberculosis. If left untreated or not properly treated, it could lead to progressive tissue damage and even death. Short-term chemotherapy containing isoniazid, rifampicin. and pyrazinamide were proven to be very effective in the treatment of TB. However, the concern regarding its potential hepatotoxicity might hinder the completion of treatment. Information regarding risk factor of hepatotoxicity among Indonesian tuberculosis patients were limited. This study aimed to investigate risk factors of hepatotoxicity among Indonesian tuberculosis patients. This was a case-control study with retrospective approach conducted at one of the public hospital in Lampung, Indonesia. We included 320 tuberculosis patients who were classified as case (64 patients who were diagnosed with hepatotoxicity during hospitalization) and control (256 patients). Results of multivariate logistic regression analysis showed that age was significant risk factor of hepatotoxicity (adjusted odds ratio (OR) 1.056, 95% CI 1.0121, 1.091), while longer duration of hospitalization had a 1.4 lower odds of hepatotoxicity compared to control (adjusted OR 0.757, 95% CI 0.682, 0.839) (p<0.005). The results indicated that older patients were more likely to have hepatotoxicity, while patients with shorter duration of hospitalization tend to have higher risk of hepatotoxicity. In conclusion, age was the risk factor associated with hepatotoxicity among tuberculosis patients.Keywords: tuberculosis, hepatotoxicity, age, hospitalization